PENERAPAN AUGMENTED REALITY PADA MEDIA PEMBELAJARAN PEMINTALAN SERAT BUATAN BERBASIS ANDROID (studi kasus : SMK Texmaco Semarang) - Setiyo Prihatmoko; Fajar Kurniawan (Pixel :Jurnal Ilmiah Komputer Grafis, 2020)
This research produces Artificial Fiber Spinning Learning Media that applies Augmented Reality (AR) for Class XI Students of TPSB SMK Texmaco Semarang as a learning aid. so that it can be used as a modern, effective, and interactive learning medium. This application was made with the aim of completing the limitations of depicting objects in existing learning media, helping students to more easily learn the material, improving student learning outcomes, and increasing the variety of media in learning. This study uses the Research and Development (RnD) method, using 6 out of 10 research stages, namely potentials and problems, data collection, product design, design validation, design improvement and product testing. The final result of making this learning media is an application in the format android application, used on every android-based mobile phone. The validity value of the media expert obtained a value of 3.2 which was declared feasible, the results of the material expert validation test obtained a value of 3.6 which was declared very feasible, and was able to increase the average value of the artificial fiber spinning subject class XI TPSB SMK Texmaco Semarang which Initially 61.5% with 17 students who had not reached the KKM to 80.5% with 4 students who had not reached the KKM.